Ticks and tick-borne disease control: proceedings of a joint OAU, FAO and ILRAD workshop - Dolan, T.T. (1993)
Proceedings of a workshop on "Ticks and tick-borne disease control" bringing together scientists and those responsible for tick-borne disease control in countries of eastern, central and southern Africa to discuss recent research findings applicable to these diseases and to address problems encountered in their control; presents current and future methods of diagnosis, novel vaccines for tick-borne diseases and vaccines against ticks, and assesses impact and economics of disease control. Includes recommendations particularly on the setting up of a committee with responsibility to draft new standards for live vaccines for tick-borne diseases.